Enhancing customer loyalty through product innovation and perceived value: A study on customers batik in Bekasi District, West Java, Indonesia - Setyaningrum, Retno Purwani (Linguistics and Culture Review, 2021)
This study aims to investigate the factors considered as important by consumers of Batik fabric created by entrepreneurs in Bekasi, West Java, Indonesia, and the relation to the customer satisfaction level. This research is quantitative research where data were collected using self-administered questionnaires distributed in the Bekasi district in West Java province. To test the relationship modeling between variables, this study used Structural Equation Modeling using Amos 16.0 software. Data were collected using questionnaires which distributed to respondents targeted with the help of enumerators. The results show that innovation and perceived value can increase customer satisfaction, which then has an impact on increasing customer loyalty and trust. In other words, customer satisfaction only serves as a bridge between innovation and perceived value with customer loyalty and trust. This is because there is no direct influence between innovation and perceived value on customer loyalty. Customer loyalty is an important aspect for Batik entrepreneurs in Bekasi in developing their business. Customers are satisfied with what they get from the innovative efforts of entrepreneurs in Batik production in Bekasi. This indicates that customer satisfaction can increase customer loyalty and trust to use a particular product.